Well-being, context, and everyday activities in space and time - Schwanen, T; Wang, D (Taylor and Francis, 2014)
Against the background of increased interest in subjectively experienced well-being in economics, psychology, and the social sciences, this article analyzes how such well-being is associated with geographical context, social contacts, and life circumstances. The empirical analysis of data collected in Hong Kong is used to elaborate and support two main claims. The first is that geography matters to not only overall well-being but also momentary well-being and that researchers should be careful to specify the influence of geographical context correctly. We therefore employ an approach that is informed by various strands of time-geographical thought and find that life satisfaction is associated more strongly with geographical context than is momentary well-being. Second, we confirm positive relations between social contacts and experienced well-being but extend earlier research by showing that these relations stretch across multiple timescales and depend to some extent on the duration of an activity episode and with whom the activity episode is undertaken. This means that the use of simple indicators of social capital is inadequate for making the complex linkages between well-being and people's social contacts understandable in empirical research.